História e memória: um estudo sobre a violência na infância com base em relatos de idosos de Goiás - ALMEIDA, Gizela Bastos da Mota (2007)
The present dissertative paper presents the process and the result of a search named MEMORY AND HISTORY: : a study about violence in the infant based in the elderly report from Goiás. Articule in the search line of Formation and teaching Professionalization, mainly, the Politics Public project and Infant Education in Goiás: history, conceptions, projects amd practice, connecting the Program of Post- Graduation Mastery from the Faculdade de Educação/UFG, this study has as its goal know the repreentations and conceptions from the infant and the education, taken from elderly, citizens from São Luís de Montes Belos GO. Intended to investigate the caracteristcs of the education process of the children in the half first of the last century and the possible relation from violence establish in this process. Based on the social-historical view and dialectic, used the oral report and interview as the way of obtain information and necessary knowledge of the internalization from the object of investigation. The search universy constitute of 23 interviewed, 10 Sirs and 13 madams between 60 and 94 years old, and the collect of the datas happened in the period from 2005 to 2007. Tried, by the ways of the found analyses, understand the dinamic from the relation intrafamiliars, as the era of the education process, as the caracteristcs socialeconomics and politics from Goiás and the living in that historical period. The relation between parents and sons were the object of the investigation, mainly in the case that refers to the authority and the ways how they educated and corrected their sons. The way of the teaching in the State made interesting for the major understanding from the peculiar of the period and the context where the people from the search came from in their infant. In this way, tried to reveal the presence or not from violence in this phase of people life as well as express about the infant and education. The caracteristics of familiar life, of education and of the habit of the period ilustrate the representation of the infant in that period.